PENEMUAN HUKUM IN CONCRETO DALAM KEBEBASAN BERAGAMA DAN BERKEYAKINAN - Alef Musyahadah Rahmah; Tedi Sudrajat (Faculty of Law, Universitas Jenderal Soedirman, 2009)
The implementation of freedom of religion and beliefs have many problems. it can be recognize by many regulation that not synchronized. Based on the research, to find in concreto’ law, researcher using the general principle’s of legal drafting. Lex superior derograt legi inferiori between article 28-29 UUD 1945 with Law No.1 Year 1965 jo Law No.5 Year 1969, Lex Specialist derograt legi generali between Law No.39 Year 1999 jo Law No.12 Year 2005 with Law No.1 Year 1965 jo Law No.5 Year 1969, and Lex posterior degograt legi priori between Law No.39 Year 1999 jo Law No.12 Year 2005 with Law No.1 Year 1965 jo Law No.5 Year 1969. Kata kunci: Hukum in Concreto, Asas-asas umum peraturan oerundang-undangan dan kebebasan beragama dan berkeyakinan